Effect of anisotropy on fracture toughness of sandstone by SCB specimen - Funatsu, T.; Takahashi, T.; Kuruppu, Mahinda (Korean Society of Rock Mechanics, 2012)
The deformation and strength properties of rocks are often affected by internal structures of rock, such as bedding planes, microcracks, etc. These structures may cause the mechanical anistorpy, and crack growth may be also affected the internal structures. In this study, we use the sedimentary rock sample having the bedding planes. There are two main aims in this study. The purposes of this research are: 1) To investigate relationship between fracture toughness and loading axis with respect to bedding planes. 2) To investigate relationship between fracture toughness and other mechanical properties of rock. The mechanical properties investigated other than fracture toughness are uniaxial compressive strength, Young’s modulus, Poisson’s ratio and P-wave velocity. The experimental results indicate that Kimachi sandstone shows anisotropic properties of Young’s modulus, tensile strength and mode I fracture toughness, but little anisotropy of uniaxial compressive strength, Poisson’s ratio and P-wave velocity.